2011
DOI: 10.1007/s10493-011-9457-1
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of some plant essential oils against Varroa destructor (Acari: Varroidae), an ectoparasitic mite of Apis mellifera (Hymenoptera: Apidae)

Abstract: This experiment was conducted to evaluate acaricidal activity of the essential oils of Thymus kotschyanus, Ferula assa-foetida and Eucalyptus camaldulensis against Varroa destructor under laboratory conditions. Moreover, fumigant toxicity of these oils was tested on Apis mellifera. After preliminary dose-setting experiments, mites and honey bees were exposed to different concentrations of the oil, with 10 h exposure time. Essential oil of T. kotschyanus appeared the most potent fumigant for V. destructor (LC(5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Some studies revealed satisfactory results from the use of several essential oils for insect management such as the cosmopolitan pest house fly, Musca domestica L. (PAVELA, 2008); malarian vector mosquito, Anopheles gambiae Giles (McALLISTER & ADAMS, 2010); parasitic mites of the honeybees bee Varroa destructor (ANDERSON & TRUEMAN, 2000); Acari: Varroidae (GHASEMI et al, 2011); and the maize weevil adults, Sitophilus zeamais Motschulky (FAZOLIN et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies revealed satisfactory results from the use of several essential oils for insect management such as the cosmopolitan pest house fly, Musca domestica L. (PAVELA, 2008); malarian vector mosquito, Anopheles gambiae Giles (McALLISTER & ADAMS, 2010); parasitic mites of the honeybees bee Varroa destructor (ANDERSON & TRUEMAN, 2000); Acari: Varroidae (GHASEMI et al, 2011); and the maize weevil adults, Sitophilus zeamais Motschulky (FAZOLIN et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One of these methods consists of using plant extracts. Secondary metabolites of some of the plants have an important role to play in withstanding pest damages, so the use of these plant derivatives could replace chemical acaricides in the control of mites (Kim et al, 2005;Ghasemi et al, 2010). In addition, when compared with chemical pesticides, plant extracts are more compatible with ecosystems, less toxic to mammals and non-target organisms, and leave no persisting materials in nature (Georges et al, 2007;Liu et al, 2005).…”
mentioning
confidence: 99%
“…Although up until now thyme has been mostly used for its pharmaceutical qualities and as a medicinal plant, now there is evidence that it should be also used as an acaricide and an insecticide. However, more studies are needed to confirm such properties (Ghasemi et al, 2010;Wandscheer et al, 2004;Akbarinia, Mirza, 2008). Beekeepers can monthly do one practice to manage Varroa mites in their colonies using mechanical methods (e.g., sprinkling honey bees with sugar syrup).…”
mentioning
confidence: 99%
“…For most E. camaldulensis EOs, 1,8-cineole is the major constituent. This oxygenated monoterpene has been found in quantities superior to 50% in EOs produced by plants cultivated in Egypt (60.3%) [63], the Democratic Republic of the Congo (58.9%) [53], Nigeria (70.4%) [67], Brazil (52.8%) [70,71] and Iran (74.7%) [69]. Plants cultivated in Kenya [78], Northern Cyprus [64] and Argentina [75,76] …”
Section: Eucalyptus Camaldulensismentioning
confidence: 99%
“…The acaricide activity of essential oils from E. camaldulensis on V. destructor mite was also investigated and a LD50 of 1.74 µL/L of air was found [69].…”
Section: Acaricide Activitymentioning
confidence: 99%